2020
DOI: 10.3390/su12219020
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Dry-Out Capability of Steel-Faced Mineral Wool Insulated Sandwich Panels

Abstract: Moisture dry-out from steel-faced insulated sandwich panels has previously received little attention from researchers. This paper reports the results from laboratory tests and dynamic heat, air, and moisture transport simulations of the moisture dry-out capabilities of a steel-faced sandwich panel with a mineral wool core. Three test walls (TWs) with dimensions of 1.2 m × 0.4 m × 0.23 m were put above water containers to examine the moisture transport through the TWs. A calibrated simulation model was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have been carried out to investigate the maintenance/loss of sealing using adhesive tapes. It has been established that the hygrothermal behaviour of steel-faced insulated sandwich panels can be controlled using adhesive tapes [5,6]. The tape is seen as a viable solution when it is required to ensure the level of tightness of a wooden frame [7]; however, it is understood that the durability of adhesion is not sufficient to ensure the good tightness of the joint for a long period [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out to investigate the maintenance/loss of sealing using adhesive tapes. It has been established that the hygrothermal behaviour of steel-faced insulated sandwich panels can be controlled using adhesive tapes [5,6]. The tape is seen as a viable solution when it is required to ensure the level of tightness of a wooden frame [7]; however, it is understood that the durability of adhesion is not sufficient to ensure the good tightness of the joint for a long period [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research [1] showed that after 8 months of outdoor aging, some of the exterior air barrier tapes, glued to the outer wall of the barrack hut from plywood panels, completely or largely peeled off from the glued surface, while others showed a change in color, bubbling, or other signs of degradation. A maintaining/losing the sealing purpose of self-adhesive tapes, as well as finding promising solutions to ensure the airtightness of the building are investigated mostly [2][3][4][5][6][7][8][9][10]. However, very few studies aim to investigate the aging of tapes and the factors influencing the deterioration of tapes' properties.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it possible to form a clearly defined area where air must move to dry the structure. As diffusion drying from a steel-faced mineral wool insulated sandwich panel is limited [9], convection drying is a method to increase the efficiency of moisture dry-out. However, there is still relatively limited research on this field.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture dry-out at stable temperature conditions (Figure1). Diffusive drying 2020 refers to a previous research on vapour retarding and vapour permeable tape performance[9].…”
mentioning
confidence: 99%